Revista Veja e a cobertura jornalística sobre o colapso do bloco soviético (1989-1992) - Marques, Sabrina Rodrigues (2017)
Revista Veja and the journalistic coverage on the collapse of the Soviet block (1989- 1992) This research takes as object of study the magazine Veja and the journalistic coverage on the collapse of the Soviet block between the years 1989 to 1992. This research aims to understand how Veja made its coverage during the first four years of economic and political crises that resulted. In the collapse of the Popular Democracies and the USSR (Union of Soviet Socialist Republics). In addition, we seek to understand how Veja's political positioning was in relation to the processes of restoration of capitalism within the countries of the Soviet bloc. The research methodology will be the critical reading of Veja texts and speeches, especially, stories, reports and images. See how the press and the party acts as an ideological face of capital fulfilling its role in shaping opinion and spreading neoliberal ideology.